The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1155/2022/2170839
|View full text |Cite
|
Sign up to set email alerts
|

LSGDM with Biogeography-Based Optimization (BBO) Model for Healthcare Applications

Abstract: Several studies aimed at improving healthcare management have shown that the importance of healthcare has grown in recent years. In the healthcare industry, effective decision-making requires multicriteria group decision-making. Simultaneously, big data analytics could be used to help with disease detection and healthcare delivery. Only a few previous studies on large-scale group decision-making (LSDGM) in the big data-driven healthcare Industry 4.0 have focused on this topic. The goal of this work is to impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…The results are tested using the KDDCup99 dataset [ 23 ] comprising different classes and 41 features. The results show that the DNN model has gained lower outcomes with the accu y of 91.64%, whereas the LSTM-RNN and GRU-RNN techniques have resulted in moderately reasonable accu y of 93.39% and 92.63%, respectively [ 35 – 38 ]. Moreover, the DBN and CNID models have accomplished considerable accu y values of 95.22% and 98.54%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The results are tested using the KDDCup99 dataset [ 23 ] comprising different classes and 41 features. The results show that the DNN model has gained lower outcomes with the accu y of 91.64%, whereas the LSTM-RNN and GRU-RNN techniques have resulted in moderately reasonable accu y of 93.39% and 92.63%, respectively [ 35 – 38 ]. Moreover, the DBN and CNID models have accomplished considerable accu y values of 95.22% and 98.54%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Figure 4 depicts the global sensitivity, specificity, and precision analysis of the FSHDL-HDDC method after 10 iterations. e results revealed that the FSHDL-HDDC algorithm had reached improved outcomes under every iteration [28][29][30][31][32]. For instance, with iteration-1, the FSHDL-HDDC method has offered sens y , spec y , and prec n of 98.17%, 97.12%, and 97.58%, respectively.…”
Section: Experimental Validationmentioning
confidence: 97%
“…Furthermore, the Euclidean distance is executed for defining the distance in a CH to BS. Using minimum distance, the energy consumption is kept significantly low [38,[54][55][56][57]. When the distance is increased, additional energy is expended.…”
Section: Algorithm 1: Tlbo Algorithmmentioning
confidence: 99%